Analysis of Differences in Students' Thinking Styles on Reading Comprehension of the Third Semester Students at IAIN Parepare - Indirwan Priyatno N; Kalsum Kalsum; Muhammad Yunus Nurdin; Jumardin Muchtar (JELITA, 2024)
The aims of this study were to find out the thinking styles of the third semester students of English Education at IAIN Parepare. It is also to know the type of dominant thinking style possessed by the third semester students of the IAIN Parepare English Study Program. This research has significance for teachers, students and future researchers. This study uses a quantitative descriptive. The research sample was 20 Semester III students of the English Education Program at IAIN Parepare. The instruments used were questionnaires and quantitative analysis. The results of the data show that the thinking style of the third semester students of English Education at IAIN Parepare refers to the indicators showing the chosen global style of 28.74% with a focus on general reading texts. Local style is 29.45 % by paying attention to details and specific information on reading texts, external style is 19.52% by collaborating with other people in answering reading tests. Internal style is 22.29 % by preferring to rely on personal activities in reading. The dominant type of thinking style possessed by third semester students of the English Language Study Program IAIN Parepare refers to indicators showing that local style becomes the dominant thinking style by paying attention to details, solving problems by following certain rules, preferring to do reading assignments. projects and implement their own ideas. Evidenced by the dominant score with 29.45 %.